KARAKTERISTIK RAGAM GERAK DAN TATA RIAS-BUSANA TARI NGREMO SEBAGAI WUJUD PRESENTASI SIMBOLIS SOSIO KULTURAL - -, Wahyudiyanto (Imaji: Jurnal Seni dan Pendidikan Seni, 2015)
Ngremo course, the theme of the dance is moving from ritual to political one so that the present growth looks like soldier dance. The heroic value embodied in the dance theme is identified as the spirit of struggle to get independence. The heroic theme is visualized in the dance movement, costume and makeup. In the movement aspect, the changes are from soft to fast speed, and supple to stiff moves. The costume is adopted from East Javanese prince’s attributes worn in the independence war. Ngremo dance, which spreads around Surabaya, therefore represents the imaginary figure of Cakraningrat and the gallant, authoritative and resolute Sawunggaling. Key words: Ngremo, characteristic and heroic dance is presented to begin Ludruk performance. In its